PERAN KUD LUBER DALAM MENINGKATKAN PENDAPATAN ANGGOTA DESA MUKTI JAYA KECAMATAN RIMBA MELINTANG KABUPATEN ROKAN HILIR - Yuslina, Eva Yuslina Eva; Indrawati, Henny Indrawati Henny; ', Ngadlan Ngadlan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: KUD is a cooperative business of department population and area the country side. KUD Luber Mukti Jaya is the rural economy and the role of subsidized distributor as a fertilizer. This research aimed at KUD Luber know how to increase its role the income, constraint members of the increasing income, and KUD what is the solution to solve the problem. Using research is a qualitative data and technical this collection conducted in an interview that and the observations. The population of this research is 145 person. The drawing of sample is purposive sampling with the number of land that have been adjusted to member of the members who have 1 hektar. The new formula is based on the calculation of Slovin with 5 % of the level of error. After doing the calculations of sampling was 86 reponden. Research shows that KUD Luber has a role to enhance its earnings and revenue could be seen from the analysis of this member. Income from analisi be higher than before being a member. Facing constraint KUD Luber to enhance income the member several members of the member that does not participate in the training education carried out by KUD Luber, and the problem is in the distribution of any fertilizer. A solution used KUD Luber to overcome the problem of absence of members by doing approach with groups and to delay fertilizer solution the board kud luber obliged to provide stock in KUD Luber for the next three weeks.Keywords : The role of KUD Luber, income members